The making of a syndrome: Gerstmann's patients before Gerstmann syndrome. (October 2022) - Cubelli, Roberto; Rusconi, Elena
Abstract: When Gerstmann published the case report which later became known as the first case of Gerstmann syndrome, he did not claim the discovery of a new syndrome. It was only a few years later, after reporting on another two similar cases, that he isolated the famous tetrad of symptoms (finger agnosia, right–left disorientation, agraphia and acalculia) as a meaningful cluster with both localising and functional value. In this article, we provide the translation of key-excerpts of the second of Gerstmann's reports (Gerstmann, 1927) and a synoptic description of the symptoms as reported in the three original cases, which were later identified as cases of Gerstmann syndrome. The descriptions appear highly consistent across cases. Among symptoms, finger agnosia stands out for its pervasiveness, which may explain why Gerstmann considered this as the core symptom and speculated it could subtend all symptoms. However, no common functional denominator emerges from the original descriptions.